Get it while it's hot: Benefits of a large herbivore exploiting stochastic resource pulses in a time of food scarcity - Samantha P. H. Dwinnell; Larissa T. Beumer; René van derWal; Steve D. Albon; Åshild Ø. Pedersen; Øystein Holand; Brage B. Hansen; R. Justin Irvine; Erik Ropstad; Vebjørn Veiberg; Leif Egil Loe (Ecosphere)
Abstract To persist in seasonal environments, animals track, exploit, and store energy when food is plentiful. Seasonal changes in plant phenology that are predictable allow animals to track abundant food resources. However, little is known about how animals use and benefit from ephemeral and unpredictable food pulses during times when food is scarce. Climate change is altering the timing, abundance, and spatial distribution of food releases, emphasizing the ongoing need for understanding how unseasonal weather conditions influence access to food. Using 12 years of GPS‐location data and annual measures of body mass in 72 adult female Svalbard reindeer (Rangifer tarandus platyrhynchus), we tested whether individuals with greater use of nutritionally beneficial resource pulses in autumn and early winter are heavier going into parturition in spring. Additionally, we evaluated how stochastic weather conditions influence the use of food resources. Reindeer that foraged most in marshes during autumn and early winter gained a positive carryover effect of up to 5 kg heavier body mass in late winter, with previously demonstrated benefits to both survival and reproduction. Marsh use was rare, brief, and intense, which is the expected response to a pulsed resource. The extent to which marshes were used varied greatly among years and was associated with stochastic mild spells that relaxed constraints of snow depth for a few days. Compared with other habitats used, marshes offered superior quantity and quality of belowground plant biomass that may be accessed more easily under milder autumn and winter conditions. Our findings demonstrate the individual benefits of exploiting stochastic food pulses and showcase how resource tracking during periods of food scarcity may be a behavioral trait that could enhance population resilience in a rapidly warming climate.